Chorionicity and Heritability Estimates from Twin Studies: The Prenatal Environment of Twins and Their Resemblance Across a Large Number of Traits - van Beijsterveldt, C. E. M. (Behav Genet, 2015)
There are three types of monozygotic (MZ) twins. MZ twins can either share one chorion and one amnion, each twin can have its own amnion, or MZ twins can—like dizygotic twins—each have their own chorion and amnion. Sharing the same chorion may create a more similar/dissimilar prenatal environment and bias heritability estimates, but most twin studies do not distinguish between these three types of MZ twin pairs. The aim of this paper is to investigate the effect of chorion sharing on the similarity within MZ twin pairs for a large number of traits. Information on chorion status was obtained for the Netherlands twin register (NTR) by linkage to the records from the database of the dutch pathological anatomy national automated archive (PALGA). Record linkage was successful for over 9000 pairs. Effect of chorion type was tested by comparing the within-pair similarity between monochorionic (MC) and dichorionic (DC) MZ twins on 66 traits including weight, height, motor milestones, child problem behaviors, cognitive function, wellbeing and personality. For only 10 traits, within-pair similarity differed between MCMZ and DCMZ pairs. For traits influenced by birth weight (e.g. weight and height in young children) we expected that MC twins would be more discordant. This was found for 5 out of 13 measures. When looking at traits where blood supply is important, we saw MCMZ twins to be more concordant than DCMZ’s for 3 traits. We conclude that the influence on the MZ twin correlation of the intra-uterine prenatal environment, as measured by sharing a chorion type, is small and limited to a few phenotypes. This implies that the assumption of equal prenatal environment of mono- and DC MZ twins, which characterizes the classical twin design, is largely tenable. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10519-015-9745-3) contains supplementary material, which is available to authorized users.